2013
DOI: 10.1039/c2an36189b
|View full text |Cite
|
Sign up to set email alerts
|

Automated surface sampling of lipids from worn contact lenses coupled with tandem mass spectrometry

Abstract: The deposition of biological material (biofouling) onto polymeric contact lenses is thought to be a major contributor to lens discomfort and hence discontinuation of wear. We describe a method to characterize lipid deposits directly from worn contact lenses utilizing liquid extraction surface analysis coupled to tandem mass spectrometry (LESA-MS/MS). This technique effected facile and reproducible extraction of lipids from the contact lens surfaces and identified lipid molecular species representing all major … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 21 publications
0
26
0
Order By: Relevance
“…Lipid profiles were compared to those obtained from human plasma and revealed that long chain polyunsaturated cholesterol esters and some SMs were significantly enhanced in plaques. LESA has also been successfully employed for the analysis of lipid deposits on worn contact lenses in an effort to understand the origins of contact lens discomfort and spoilage [231]. Lipid classes detected included PC, SM, cholesterol esters, wax esters and O-acyl--hydroxy fatty acids.…”
Section: Liquid Extraction Surface Analysis (Lesa)mentioning
confidence: 99%
“…Lipid profiles were compared to those obtained from human plasma and revealed that long chain polyunsaturated cholesterol esters and some SMs were significantly enhanced in plaques. LESA has also been successfully employed for the analysis of lipid deposits on worn contact lenses in an effort to understand the origins of contact lens discomfort and spoilage [231]. Lipid classes detected included PC, SM, cholesterol esters, wax esters and O-acyl--hydroxy fatty acids.…”
Section: Liquid Extraction Surface Analysis (Lesa)mentioning
confidence: 99%
“…In contrast to other ambient analysis techniques mentioned above, the process of surface sampling and ionisation are decoupled, offering opportunities for superior quantification. Whilst LESA has shown promise for the profiling of proteins, lipids, drugs and metabolites in tissue and blood [10][11][12][13], its potential application to the chemical profiling of other biological fluids has not yet been considered.…”
Section: Introductionmentioning
confidence: 99%
“…Liquid Extraction Surface Analysis (LESA) [9][10][11][12][13] is a new tool in surface mass spectrometry, which also operates under ambient conditions and has recently become commercially available. The technique involves the deposition of a solvent droplet from a pipette tip onto a surface.…”
Section: Introductionmentioning
confidence: 99%
“…84 Such “contact” model LESA may be advantageous for the analysis of samples containing a protective layer on the surface. When installed on a fully automated robotic system, it enables high-throughput, spatially resolved analysis of metabolites, 85,86 lipids, 8790 and proteins 91,92 in complex samples, including dried blood spots, 84,88 contact lenses, 89 tissues, 55,83,86,91 and microbial colonies. 84,93 LESA also has been used for analyzing molecules separated using TLC 83 and capillary electrophoresis.…”
Section: Ambient Liquid Extraction Techniquesmentioning
confidence: 99%